Trends in Spontaneous and Medically Indicated Preterm Birth in Twins versus Singletons: A California Cohort 2007 to 2011 - Ness, Amen; Mayo, Jonathan A.; El-Sayed, Yasser Y.; Druzin, Maurice L.; Stevenson, David K.; Shaw, Gary M. (American Journal of Perinatology, 2021)
Objective The study aimed to describe preterm birth (PTB) rates, subtypes, and risk factors in twins compared with singletons to better understand reasons for the decline in PTB rate between 2007 and 2011.Study Design This was a retrospective population-based analysis using the California linked birth certificates and maternal-infant hospital discharge records from 2007 to 2011. The main outcomes were overall, spontaneous (following spontaneous labor or preterm premature rupture of membranes), and medically indicated PTB at various gestational age categories: <37, <32, and 34 to 36 weeks in twins and singletons.Results Among the 2,290,973 singletons and 28,937 twin live births pairs included, overall PTB <37 weeks decreased by 8.46% (6.77–6.20%) in singletons and 7.17% (55.31–51.35%) in twins during the study period. In singletons, this was primarily due to a 24.91% decrease in medically indicated PTB with almost no change in spontaneous PTB, whereas in twins indicated PTB declined 7.02% and spontaneous PTB by 7.39%.Conclusion Recent declines in PTB in singletons appear to be largely due to declines in indicated PTB, whereas both spontaneous and indicated PTB declined in twins.Key Points
Keywords: twins; preterm birth; trends; spontaneous preterm birth; medically indicated preterm birth